University teacher training. From LOGSE to Science in Parliament - Flecha García, José Ramón (Avances en Supervisión Educativa, 2019)
Teacher education in the countries with better academic results has been carried out since the 80s based on the evidence contributed by research supported by the international scientific community (Toom, A. et al., 2010). This article presents some of the results from three projects from the European scientific research programmes: Workaló (FP5), Included (FP6) and Impact (FP7). The communicative methodology of research is now a requirement for the next European scientific programme (Horizon Europe) which demands a constant dialogue based on arguments and evidence between the research staff and the citizenship involved. In the studies in which the content of this article is based, the communicative methodology of research has been followed with 17 seminars, the first of which began in 2000, with kindergarten, primary and high school teachers. Today, the seminars gather biweekly or monthly from 8 participants in one of them to 187 in another one. The results exposed here are focused on five of the transformative elements which are now improving the situation in Spain after in the 80s the aforementioned training was not based on scientific evidence validated internationally: scientific evidence internationally validated: the meritocratic reform of the universities, the fight against gender violence in our universities, the democratic revolution of knowledge, the progressive Europeanization in our education and schools which show in practice that based on scientific evidence, and not on assumptions, is how results are improved.
Keywords: teacher training; scientific knowledge; gender violence